Preparation of women for breast-feeding - Gebuza, Grażyna; Gierszewska, Małgorzata; Kaźmierczak, Marzena; Michalska, Estera; Kotzbach, Roman (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. The advantages of breast-feeding for both mother and child are incontrovertible. Humans’ milk is the only safe product to feed an infant, as milk is perfectly adjusted to its infant’s gastrointestinal tract. Breast-feeding ensures optimum development and health. An essential factor in breastfeeding is a certain level of knowledge and skills. It is a midwife who should recognize and estimate the level of patient’s knowledge according to her own diagnosis and plan the educational process based on the proper teaching methods. An important issue to succeed in breastfeeding is help during the first time of this action. Finally, a midwife is supposed to provide an emotional support. Aim of the study. The aim of this thesis was evaluation of the awareness on the advantages of Breast-feeding among women bearing first child in the maternity ward of the L. Rydygier Provincial Policlinical Hospital in Torun. As a method a survey was chosen and a developed solely for this purpose questionnaire was used. Material and methodos. The research technique was the author’s survey, which comprises of 27 question from the field of knowledge about advantages of breast-feeding and the procedure during lactation. The filling of the questionnaire was voluntary and anonymous. The survey was conducted between 1st and 22nd of April 2008 in the maternity ward of the L. Rydygier Provincial Policlinical Hospital in Torun. 100 randomly chosen women in childbirth were surveyed. Results. For the majority of surveyed women the priority of breast-feeding is child’s health. The majority of women know the influence of breast-feeding on child’s health. For the majority of surveyed women breast-feeding is an important element of the emotional bond with a newborn child. The significant majority of women searched for the information on the subject of breast-feeding and stated that gaining knowledge on this subject is necessary. The surveyed women know what factors hinder breast-feeding and inhibit lactation. Conclusions. The analysis of the gathered material shows that the surveyed women had a varied scope of knowledge and skills. The survey shows the necessity of a planned and systematic education, which would be adapted to individual needs of the women after birth. Nursing Topics 2010; 18 (4): 406-412